Challenges and opportunities of the transition for online teaching on a portuguese school of education - Correia, Marisa (2022)
The global intensification of academic work (McInnis, 2010) and lim ited time constraints (McCune, 2018) hinders higher education teachers to foster developmental processes relating to pedagogy. However, there is evidence that higher education change, namely promoted by digital technologies, can shift higher education teachers’ roles and identities (McNaughton & Billot, 2016). Due to COVID-19 pandemic a dramatic higher education contextual change had occurred related to a rapid shift for online environments. According to Major (2020), higher education teachers have done an amazing job in putting workable short-term technological solutions for online teaching and learning, many of them with synchronous activities using video-conferencing apps such as Zoom® and Skype®. This movement pushed forward educational innovation, although without time to prepare a pedagogical development plan for academics about virtual learning environments. Offering high-quality instruction re quires a huge amount of planning and work, including reframing and reconceptualizing communication, engagement, and community (Ma jor, 2020). This exploratory study focuses on which challenges and opportunities teachers of a higher education institution (HEI) faced on their teaching experiences along the transition period for online education during the COVID-19 pandemic. Our intention was to understand how teachers were dealing with this new and complex situation, in order to be able to develop support strategies that could respond to the needs of the educa tional community. It was also our concern to obtain information that would contribute to a better preparation and organization of the follow ing school years. Therefore, learning from the present to anticipate prob lems that would continue to arise in the short term.